Karakteristik Kondisi Lingkungan Fisik dan Praktik Pemberantasan Sarang Nyamuk Terhadap Kejadian Demam Berdarah Dengue di Kota Medan - Vicky Arfeni Warongan (STIKES Columbia Asia Medan, 2024)
Dengue hemorrhagic fever is a communicable disease which is caused by dengue virus and transmitted through the bite of Aedes aegypti or Aedes albopictus. The high prevalence rate of dengue hemorrhagic fever is resulted from the poor condition of physical environment and practice of mosquito nest eradication. The research objective was to know the characteristics of condition of physical environment and practice of mosquito nest eradication (referred to as PSN) toward dengue hemorrhagic fever incident in Medan, in 2024. This is an descriptive research. The population was 98 households in Medan; the samples were 49 households. The data were collected through questionnaires and observations. The data analysis methods consisted of univariates. The univariate analysis results demonstrated that the dengue hemorrhagic fever cases had higher prevalence rate in August (41%) at Puskesmas PB Selayang II (43%), and had dominant attack on 3-14 year old people (39%) as well as on females (59%). It is recommended that Puskesmas and local government are expected to work togenther in implementing mosquito nest eradication program and for the community is expected to pay attention to lighting at home an water reservoirs both inside and outside the home.